Occurrence and distribution of Scrippsiella cf. acuminata (Dinophyta, Thoracospharaceae) in a tropical estuarine gradient - Caio Ceza da Silva Nunes; Daniela Mariano Lopes da Silva; Helen Michelle de Jesus Affe; José Marcos de Castro Nunes (Rodriguésia, 2022)
Abstract Scrippsiella acuminata is a species complex that can cause anoxic conditions in the water column during blooms. This study aimed to analyze the occurrence and distribution of Scrippsiella cf. acuminata along the estuarine gradient of Paraguaçu River, from bimonthly sampling (March 2018 to March 2019) performed at 12 sampling points. Environmental variables were measured in situ, and water samples were collected for analysis of dissolved inorganic nutrients and phytoplankton cell density. At each point, samples were collected for analysis of species composition and preserved with formaldehyde at a final concentration of 4%. S. cf. acuminata occurred throughout the estuarine gradient (salinity 0.1–38.9), except in July, coinciding with the lowest concentrations of dissolved inorganic nutrients. Cell density varied between 20 cel L-1 (January 2019) and 1.8 × 106 cell L-1 (March 2018); in the latter, the species bloomed under conditions of low salinity (5.7) and the highest dissolved inorganic nutrient concentration recorded in the study. Cell density (1.7 × 105 L-1) increased in November 2018. Neither event had any detrimental effects on the estuarine system. This study allowed us to better understand the distribution patterns of S. cf. acuminata considering the environmental characteristics that can favor its development.